PENDAMPINGAN GURU PAI DALAM PENYUSUNAN PPT PEMBELAJARAN JARAK JAUH (PJJ) DI MASA PANDEMI COVID-19 DI HARJAMUKTI KOTA CIREBON - AISYAH AISYAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This Best Practice aims to assist Islamic Religious Education teachers in the preparation of Distance Learning PowerPoint (PJJ) during the COVID-19 pandemic in Harjamukti District, Cirebon City. The subjects of this assistance were 19 PAI teachers in the Harjamukti sub-district, Cirebon city. So the focus of this journal is on assisting PAI teachers in the preparation of Powerpoint. There are three stages of this assistance, including: stage one, namely planning, stage two of implementation, and stage three of evaluation. The results of this mentoring are as follows: 1) The 1st mentoring PAI teachers have not mastered the preparation of PowerPoint, only 32% of PAI teachers are good. 2) The second mentoring has an increase of 11% very good, 31% PAI teachers are good, 11% PAI teachers are quite good, and 47% PAI teachers are not good at making PowerPoint. 3) The 3rd mentoring is further increased by 26% of PAI teachers who are very good, 42% good, 11% quite good, and 21% of PAI teachers who are less able to make PowerPoint. 4) The 4th mentoring increased very significantly by 11% of teachers with pretty good predictions, 42% good and 47% very good. From the results of the PAI teacher mentoring, it can be concluded that the PAI teacher's ability to make PowerPoint is said to be successful through the PAI teacher's assistance in making PowerPoint. With a significant increase, it means that the assistance of PAI teachers in making PowerPoint has a positive impact on increasing the competence of PAI teachers in making PowerPoint. ABSTRAKBest Practice ini bertujuan dalam pendampingan guru Pendidikan Agama Islam dalam penyusunan PowerPoint Pembelajaran Jarak Jauh (PJJ) di masa pandemic COVID-19 di Kecamatan Harjamukti Kota Cirebon. Subyek dari pendampingan ini adalah 19 guru PAI yang ada di kecamatan harjamukti kota Cirebon. Jadi fokus jurnal ini adalah pendampingan guru PAI dalam penyusunan Powerpoint. Pendampingan ini ada tiga tahapan antaralain: tahap satu yaitu perencanaan(planning), tahap dua pelaksanaan), dan tan tahap tiga evaluasi. Adapun hasil dari pendampingan ini sebagai berikut: 1) Pendampingan ke-1 guru PAI belum menguasai penyusunan PowerPoint hanya 32% guru PAI sudah baik. 2) Pendampingan ke-2 ada peningkatan sebanyak 11% amat baik , 31% guru PAI sudah baik, 11% guru PAI cukup baik, dan 47% guru PAI kurang baik dalam membuat PowerPoint. 3) Pendampingan ke-3 lebih meningkat lagi sebanyak 26% guru PAI sudah amat baik, 42% baik, 11% cukup baik, dan 21% guru PAI yang kurang mampu dalam membuat PowerPoint. 4) Pendampingan ke-4 meningkat sangat signifikan sebanyak 11% guru dengan predikan cukup baik, baik 42% dan amat baik sebanyak 47%. Dari hasil pendampingan guru PAI tersebut, dapat disimpulkan bahwa kemampuan guru PAI dalam membuat PowerPoint dikatakan berhasil melalui pendampingan guru PAI dalam membuat PowerPoint. Dengan peningkatan yang signifikan, artinya pendampingan guru PAI dalam membuat PowerPoint memberikan dampak positif terhadap peningkatan kompetensi guru PAI dalam membuat PowerPoint.